Expansion and diversity of caspases in Mytilus coruscus contribute to larval metamorphosis and environmental adaptation - Yanfei Cao; Linxiang Xu; Xinwei Xiong; Xiao Liu (BMC Genomics, 2024)
Abstract Background Apoptosis is involved (directly and indirectly) in several physiological processes including tissue remodeling during the development, the turnover of immune cells, and a defense against harmful stimuli. The disordered apoptotic process participates in the pathogenesis of various diseases, such as neoplasms, and chronic inflammatory or systemic autoimmune diseases, which are associated with its inadequate regulation. Caspases are vital components of the apoptotic pathway that are involved in developmental and immune processes. However, genome-wide identification and functional analysis of caspase have not been conducted in Mytilus coruscus, which is an economically important bivalve. Results Here, 47 caspase genes were identified from the genomes of M. coruscus, and the expansion of caspase-2/9 and caspase-3/6/7 genes were observed. Tandem duplication acts as an essential driver of gene expansion. The expanded caspase genes were highly diverse in terms of sequence, domain structure, and spatiotemporal expression profiles, suggesting their functional differentiation. The high expression of the expanded caspase genes at the pediveliger larvae stage and the result of apoptosis location in the velum suggest that the apoptosis mediated by them plays a critical role in the metamorphosis of M. coruscus larvae. In gill, caspase genes respond differently to the challenge of different strains, and most caspase-2/9 and caspase-3/6/7 genes were induced by copper stress, whereas caspase-8/10 genes were suppressed. Additionally, most caspase genes were upregulated in the mantle under ocean acidification which could weaken the biomineralization capacity of the mantle tissue. Conclusions These results provide a comprehensive overview of the evolution and function of the caspase family and enhanced the understanding of the biological function of caspases in M. coruscus larval development and response to biotic and abiotic challenges.